2023
DOI: 10.3390/jpm13071179
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Comorbid Course of Chronic Obstructive Pulmonary Disease

Abstract: (1) Background. Chronic obstructive pulmonary disease (COPD) has a heterogeneous natural history, manifested both in the variability of clinical features and in association with various comorbid pathologies. Atherosclerotic cardiovascular disease (ASCVD) is of great clinical importance and contributes significantly to the natural history and prognosis of COPD. The present study aimed to evaluate the nature of the comorbid course of COPD during a 15-year follow-up. (2) Methods: A total of 170 male COPD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As early as more than a decade ago, Topsakal et al found that the severity and intensity of atherosclerosis in COPD patients increased, and speculated that chronic OS and in ammation associated with COPD may be the cause of driving coronary atherosclerosis in these patients [26]. The occurrence of COPD patients with AS has also been continuously found in subsequent clinical studies [27,28]. A metabolomics analysis provided evidence for this phenomenon and found that the carnitine/acylcarnitine ratio of COPD patients was lower than that of healthy controls, suggesting the existence of atherosclerosis susceptibility and OS caused by insu cient fatty acid β-oxidation [29].…”
Section: Discussionmentioning
confidence: 99%
“…As early as more than a decade ago, Topsakal et al found that the severity and intensity of atherosclerosis in COPD patients increased, and speculated that chronic OS and in ammation associated with COPD may be the cause of driving coronary atherosclerosis in these patients [26]. The occurrence of COPD patients with AS has also been continuously found in subsequent clinical studies [27,28]. A metabolomics analysis provided evidence for this phenomenon and found that the carnitine/acylcarnitine ratio of COPD patients was lower than that of healthy controls, suggesting the existence of atherosclerosis susceptibility and OS caused by insu cient fatty acid β-oxidation [29].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Putcha et al showed that approximately 86% to 98% of COPD patients have at least one comorbidity (average number of comorbidities per individual = 1.2-4) [3]. The overlap between high levels of comorbidity and COPD is associated with a poor 2 of 12 clinical and prognostic outcome: poorer quality of life and increased risk of exacerbations, hospitalization, and mortality [4][5][6][7]. This finding is similar to what has been found in studies of the role of comorbid conditions in other chronic respiratory diseases, such as asthma [8,9].…”
Section: Introductionmentioning
confidence: 99%